Use of an Artificial Intelligence-Driven Digital Platform for Reflective Learning to Support Continuing Medical and Professional Education and Opportunities for Interprofessional Education and Equitable Access - Brian Cohen; Sasha DuBois; Patricia A. Lynch; Niraj Swami; Kelli Noftle; Mary Beth Arensberg (MDPI AG, 2023)
Continuing medical education (CME) and continuing education (CE) provide frameworks for assimilating and disseminating new advancements and are mainstays of clinicians' professional development and accreditation. However, traditional CME/CE approaches may be challenged in providing opportunities for integrated and interprofessional learning and helping clinicians effectively translate innovations into individual practice. This Commentary describes the reflective learning approach, including its integration into CME/CE and how it can support interprofessional education. Also identified are barriers to reflective and interprofessional learning implementation and CME/CE access. The Commentary provides insights based on point-of-care reflection data and outlines considerations in trialing the use of an artificial intelligence (AI)-driven digital platform for reflective learning. Further, the Commentary describes how the AI-driven digital platform may help overcome barriers to reflective learning and interprofessional education and support equitable CME/CE program access.